Analisis Dimensi Efektivitas Program Polri Belajar Terhadap Kinerja Anggota Polri di Polres Sukaharjo - Yuwono, Ismanto; Kosasih; Yuliaty, Farida (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study investigates the impact of the "POLRI Belajar" program on enhancing the performance of police officers at the Sukoharjo Police Resort. The program aims to improve the knowledge, skills, and work attitudes of officers in addressing the increasingly complex challenges and demands of society. This research employs a quantitative method, with data collected through a survey distributed to 83 program participants. The data is analyzed using multiple linear regression. The analysis results indicate that the three independent variables knowledge, skills, and attitude have a significant impact on performance. Specifically, the knowledge variable (X1) shows a significant influence with a coefficient of 0.630 and a significance value of 0.000. In contrast, the skills variable (X2) also has a significant effect, with a regression coefficient of -0.165 and a significance value of 0.013. Additionally, the attitude variable (X3) demonstrates a significant influence with a regression coefficient of 0.282 and a significance value of 0.000. The study concludes that the "POLRI Belajar" program considerably improves police personnel performance, notably by reinforcing knowledge, abilities, and work attitudes. This conclusion emphasizes the need of continual training inside police organizations and suggests the creation and improvement of such programs in the future. Furthermore, this study opens the door to future in-depth investigations into other elements that may impact police performance.